Combined effects of irrigation and cutting regimes on lucerne forage production - Lazaridou M.; Vrahnakis M.S. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The critical role of water on lucerne (Medicago sativa L.) plants combined with clipping on shallow, infertile soils of a sub-humid Mediterranean environment are still under consideration. The total above ground biomass (AGBt) of lucerne plants and the seasonal distribution of the AGB were studied under different combination of clipping and irrigation treatment at the first two years since the establishment. The results showed that though the influence of water shortage was more drastic at the first year, it was less evident at the second. The seasonal AGB production of the irrigated lucerne plants was distributed more uniformly as compared to the unirrigated. Also, the clipping intensity did not significantly affect the AGB production of the first year. The unclipped and unirrigated plants were favoured in the second year.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)